The best healthcare (commodity) available (for purchase): provider-induced demand for obstetric ultrasonography among ethnic minority women in rural northern Vietnam - Bronwyn McBride, PhD; Sumit Kane, PhD; John O'Neil, PhD; Liem T. Nguyen, PhD (Elsevier, 2024)
Despite Vietnam's overall progress on maternal health indicators, marginalized ethnic minorities in remote areas face lower access to antenatal care and higher maternal mortality rates relative to the Kinh (majority ethnic group). Last year, we conducted fieldwork for 2 qualitative research projects that aimed to address maternal health inequities among pregnant ethnic minority women in rural Northern Vietnam. Although not the focus of our research, the use of ultrasonography services at for-profit private clinics was ubiquitous in participants' healthcare-seeking accounts. Ultrasound scans from for-profit clinics were a major component of ethnic minority women's antenatal care: many purchased 8 to 10 scans during pregnancy at $6.15 US dollars per scan, despite their limited agricultural income of $120 to $205 per month. Women were unaware of how many scans were recommended and their medically indicated scheduling, but purchased frequent scans to assuage pregnancy anxieties and access what they experienced as the highest-quality antenatal service. In tandem, for-profit ultrasonography providers offered broader opening hours, immediate results, and rich technological scans, which seemed to deliver poor families the most tangible "value" for their hard-earned money.Previous literature documented the concerning overuse of ultrasonography among Kinh women in urban Vietnam: What are the implications of this trend extending to affect rural-dwelling ethnic minority women who face lower education, economic marginalization, and a 4-fold higher maternal mortality rate? Our findings raise concerns related to safety, financial vulnerability and provider-induced demand, and broader health policy questions regarding healthcare commodities in low-resource settings. Critically, there is no evidence of the effect of obstetrical ultrasound on reducing maternal mortality in low- and middle-income countries, and its excess use could burden available resources and detract from evidence-based services.Our findings suggest that health system gaps are driving poor women toward frequent purchases of a single insufficient maternal health commodity: this will not improve their pregnancy outcomes or health equity for marginalized ethnic minorities. We argue that addressing this overuse of ultrasonography due to provider-induced demand requires a multipronged response that meets women's growing expectations. Our findings highlight the need for investment in health education, health promotion, and reliable high-quality public maternal healthcare for ethnic minority communities in Vietnam.